Are There Any Land Use Dynamics in the Upper Bistrița Basin, Eastern Carpathians, Romania, in the Period 1990–2021? - Valentin Jujea; Valeriu Stoilov-Linu; Mihaela Boboc; Ionel Popa; Alexandru Nedelea; Nicolae Crăciun; Bogdan-Mihai Negrea (Diversity, 2023)
This paper aims to assess land use and land use change (LULC). For this purpose, supervised mapping on satellite imagery, using the European Space Agency (ESA) SNAP programme from LANDSAT databases, publicly accessible through the European Copernicus portal, was used. At the same time, an analysis of the degree of landscape fragmentation in the study area was carried out, which revealed that, because of the particular fragmentation of small polygons, the best results were obtained via analysis/supervised mapping on satellite images. This method, once validated in the field, reflects the most accurate land use pattern in the analysed area, with wide applications in studies of agriculture, biodiversity, geography, etc. Between 2000 and 2010, significant changes were registered. Artificial surfaces decreased by approximately 400 ha, showing a negative trend in the last period of the interval. Coniferous forests reached their maximum threshold in 2000 (with 114,400 ha) in conjunction with the “Grassland” class, which exceeded 16,700 ha. In 2010, a drastic decrease in “Grassland” was recorded, reaching half of the values of 1990 and 2000, now having only 15,684 ha. Land cover changes were significant when comparing the period before 1989 with 2021. This fact was due to socio-economic changes in society, in large part caused by changes in professions and the way of life of the population.